Amalgama dental : obturación funcional o simple relleno cavitario? (1994)
ABSTRACT: Amalgam continues being the most used restorative material in Dentristy. However its clinical results are not-completely successful due to an inadequate manipulation of the material, more than the material by itself. There is a complete classification of the material to know more about its development. Undoubtely with the new technology, the cavities for amalgam restorations have had great modifications when compared with the designs of the first years of century. At the end of this article are very important observations about three factors considered in order to obtain an adequate restoration: control of marginal failure, build a correct occlusal anatomy and function, and control of interproximal margins, looking for different ways so that the operator can reach better results with the amalgam by controlling the factors that he or she manipulates.